Frequent cross-species transmissions of foamy virus between domestic and wild felids. Issue 1 (12th January 2020) - Kraberger, Simona; Fountain-Jones, Nicholas M; Gagne, Roderick B; Malmberg, Jennifer; Dannemiller, Nicholas G; Logan, Ken; Alldredge, Mat; Varsani, Arvind; Crooks, Kevin R; Craft, Meggan; Carver, Scott; VandeWoude, Sue
Abstract: Emerging viral outbreaks resulting from host switching is an area of continued scientific interest. Such events can result in disease epidemics or in some cases, clinically silent outcomes. These occurrences are likely relatively common and can serve as tools to better understand disease dynamics, and may result in changes in behavior, fecundity, and, ultimately survival of the host. Feline foamy virus (FFV) is a common retrovirus infecting domestic cats globally, which has also been documented in the North American puma ( Puma concolor ). The prevalent nature of FFV in domestic cats and its ability to infect wild felids, including puma, provides an ideal system to study cross-species transmission across trophic levels (positions in the food chain), and evolution of pathogens transmitted between individuals following direct contact. Here we present findings from an extensive molecular analysis of FFV in pumas, focused on two locations in Colorado, and in relation to FFV recovered from domestic cats in this and previous studies. Prevalence of FFV in puma was high across the two regions, ∼77 per cent (urban interface site) and ∼48 per cent (rural site). Comparison of FFV from pumas living across three states; Colorado, Florida, and California, indicates FFV is widely distributed across North America. FFV isolated from domestic cats and pumas was not distinguishable at the host level, with FFV sequences sharing >93 per cent nucleotide similarity. Phylogenetic, Bayesian, and recombination analyses of FFV across the two species supports frequent cross-species spillover from domestic cat to puma during the last century, as well as frequent puma-to-puma intraspecific transmission in Colorado, USA. Two FFV variants, distinguished by significant difference in the surface unit of the envelope protein, were commonly found in both hosts. This trait is also shared by simian foamy virus and may represent variation in cell tropism or a unique immune evasion mechanism. This study elucidates evolutionary and cross-species transmission dynamics of a highly prevalent multi-host adapted virus, a system which can further be applied to model spillover and transmission of pathogenic viruses resulting in widespread infection in the new host.